EXTH-66. ENHANCEMENT OF ANTI-PD-1 THERAPY WITH EXTENDED HALF-LIFE IL-2 IS INDEPENDENT OF MHC CLASS I RESTRICTED ANTIGEN RECOGNITION FOR TREATMENT OF EXPERIMENTAL GLIOMA. (12th November 2021) - Tritz, Zachariah; Ayasoufi, Katayoun; Malo, Courtney; Himes, Benjamin; Khadka, Roman; Fain, Cori; Goddery, Emma; Yokanovich, Lila; Jin, Fang; Hansen, Michael; Parney, Ian; Wang, Chensu; et al.
Abstract: Glioblastoma (GBM) is the most common malignant brain tumor in adults, responsible for approximately 225, 000 deaths per year. Despite pre-clinical successes, therapeutic interventions have failed to extend patient survival by more than a few months. Anti-PD-1 checkpoint inhibition monotherapy has had efficacy against some tumor types but not GBM. The aim of this study was to determine whether supplementing anti-PD-1 checkpoint blockade with an engineered extended half-life IL-2 could improve outcomes in a preclinical model of disease. Our enhanced checkpoint blockade (ECB) strategy reliably cures approximately50% of C57BL/6 mice bearing orthotopic GL261 gliomas and extended median survival even in the mice that eventually succumbed. This therapy generates robust immunologic responses, features of which include secondary lymphoid organ enlargement and increased activation status of both CD4 and CD8 T cells. Further, many of the characteristics of brain-tumor mediated peripheral immunosuppression, including MHC class II downregulation on APCs, are prevented by ECB combination therapy. This immunity is durable, with long-term ECB survivors able to resist GL261 rechallenge. Notably, ECB's efficacy is independent of host MHC class I restricted antigen presentation, being equally efficacious in MHC class I and CD8 T cell deficient mice. Conversely, ECB combination therapy is reliant on CD4 T cells and their depletion abrogates the therapy's survival benefit. Our data shows ECB combination immunotherapy to be efficacious against the GL261 glioma model through an MHC class I independent mechanism, enhancing its off-the-shelf translational appeal relative to strategies requiring extensive knowledge of tumor-specific antigens.